Bituminaria basaltica (Fabaceae), a new species from Italy - Minissale, Pietro; Brullo, Cristian; Brullo, Salvatore; Del Galdo, Gianpietro Giusso; Sciandrello, Saverio (Phytotaxa, 2013)
Bituminaria basaltica is described and illustrated from Filicudi, an islet of the Aeolian Archipelago (Sicily, Italy). This new species, belonging to a small genus of Fabaceae occurring in the Mediterranean region and the Canary Islands, is morphologically distinct from the other taxa in the following features: leaf shape and size, inflorescence size, petal colour, size and shape of flowers, pods and seeds. Its relationships with the known species of Bituminaria are examined and a key to the genus is provided.